Biomechanical Regenerative Braking Energy Harvester: A Systematic Analysis - Yoon, Kyung Taek; Choi, Young Man (International Journal of Precision Engineering and Manufacturing - Green Technology, 2023)
Regenerative braking is a well-known technology applied in electric vehicles to achieve high energy efficiency through an energy-recovery mechanism. The same concept has been applied to robotic applications, such as legged robots, lower-limb prostheses, and biomechanical energy harvesters. In particular, a biomechanical energy harvester enables humans to generate watts of power while simultaneously assisting in the braking of human joints during walking. In this study, a systematic analysis of a biomechanical regenerative braking energy harvester was conducted. First, we reviewed the design considerations of each harvester component and designed an energy-harvester prototype with high power density through a systematic design process. Subsequently, the dynamics of the designed harvester and its effect on human biomechanics were analyzed through device testing and human testing. The designed harvester demonstrated a power density of 3.3 W/kg for level-ground walking during device testing. We evaluated muscle activities and joint kinematics in versatile walking scenarios such as sloped walking. In level-ground and downhill walking, the hamstring muscle activity was assisted by the braking torque simultaneously generating 1.2 W and 0.7 W, respectively, during negative work phase. Meanwhile, we confirmed that the braking torque was generated rather in the positive work phase interfering the quadriceps muscle activity. Comparing previous knee-joint-driven biomechanical regenerative braking energy harvesters, our harvester shows relatively high power density level even with slower walking speed and without any special mechanism.
Keywords: Braking torque; Device testing; Electromagnetic generators; Energy Harvester; Energy recovery; High energy efficiency; High-power-density; Muscle activities; Regenerative braking energies; Systematic analysis; Electromagnetic generator; Energy harvesting; Regenerative braking; Systematic analysis